The Effect of Liquid Organic Fertilizer Derived from Goat Manure and Banana Peel on the Growth of Pakcoy (Brassica rapa L.) Cultivated Using a Hydroponic System - Sania Nabila; M. Idris (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to examine the effects of liquid organic fertilizer (LOF) derived from goat manure and banana peels, applied either individually or in combination, on the growth and yield of pakcoy (Brassica rapa L.) cultivated in a hydroponic system as an alternative to the conventional AB mix nutrient solution. The experiment was conducted using a Randomized Block Design) with two treatment factors: goat manure LOF concentrations (0 ml, 30 ml, and 60 ml) and banana peel LOF concentrations (0 ml, 20 ml, and 30 ml). The observed parameters included number of leaves, plant height, leaf width, root length, and fresh weight. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test at a 5% significance level to determine differences among treatments. The results showed that the best single treatment was obtained from the application of 30 ml banana peel LOF at 4 weeks after planting (WAP). Moreover, the combined treatment of 60 ml goat manure LOF and 30 ml banana peel LOF (P2K2) produced the highest and significantly superior results across all observed parameters at 4 WAP, particularly in leaf number, plant height, root length, and fresh weight. These findings indicate that the combined application of banana peel and goat manure LOF effectively enhances the growth and yield of hydroponically cultivated pakcoy. Therefore, this organic fertilizer combination has strong potential to serve as a more economical and environmentally friendly alternative nutrient source for hydroponic cultivation systems.